Yakobus 2:1-13: Meninjau Pentingnya Kasih Tanpa Memandang Muka - Jonius Halawa; Abad Jaya Zega (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
In James 2:1-13, the overall message reminds us not to show favoritism. In verse 5, it is said that God has chosen the poor to become rich in faith and heirs of the kingdom of heaven. He does this for the poor, so why do humans discriminate against someone based on their wealth or possessions? This is a wrong attitude. The rich often intimidate the poor because they believe that their current wealth defines their happiness, leading some to neglect those around them (the poor). James says that the rich have blasphemed the name of Christ, but you honor them because of their wealth. Whereas the poor have never blasphemed the name of Christ, but you insult them.